Effects of processing conditions on the properties of paraffin/melamine-urea-formaldehyde microcapsules prepared by in situ polymerization - Han, Shenjie; Chen, Yanping; Lyu, Shaoyi; Chen, Zhilin; Wang, Siqun; Fu, Feng (Colloids and surfaces. A, Physicochemical and engineering aspects, 2020)
[Display omitted] Microcapsules containing phase change material (PCM) paraffin as the internal phase and melamine-urea-formaldehyde (MUF) as the external shell were synthesized by in situ polymerization in the study. The effects of processing conditions (including core-to-shell ratio, concentration of styrene/maleic anhydride (SMA), reaction temperature, reaction time, and final reaction pH) on the properties of synthesized microcapsules (microencapsulation process, morphology, mean diameter, and phase change properties) were investigated. The chemical structures, morphologies, and phase change properties of paraffin/MUF microcapsules were characterized by Fourier transform infrared spectroscopy (FTIR), field emission scanning electron microscopy (FE-SEM), differential scanning calorimetry (DSC), and thermogravimetric analyzer (TGA). Under optimal processing conditions (core-to-shell ratio of 1.5, 20 mg/mL SMA, 2-h reaction at 80 °C, and final reaction pH 5.5), the encapsulation efficiency of synthesized paraffin/MUF microcapsules reached 77.1% and the phase change latent heat values of melting and crystallization were about 134.3 J/g and 133.1 J/g, respectively.